Family Psychoeducation Therapy to Improve Family's Ability to Care for Victims of Sexual Abuse - Iva Milia Hani Rahmawati; Inayatur Rosyidah (NurseLine Journal, 2021)
Background: Sexual abuse is increasingly occurring but it is difficult to detect. Victims and their families usually do not want to reveal the sexual abuse clearly, complicates intervention efforts. The most incidents of sexual abuse occurred in children and adolescents, which is called child sexual abuse. Aim This study was conducted to analyze the effect of Family Psychoeducation (FPE) therapy on family’s ability to care for children who experienced sexual abuse (post sexual abuse) in the working area of Women's Crisis Center (WCC), Jombang Regency, East Java. Method: This study utilized pre-experimental design with one group pretest-posttest design; using one treatment group, with observations conducted to the group before and after treatment. The population in this study were all families with children who experienced sexual abuse with a total of 133 respondents. By using simple random sampling technique, 100 samples were obtained. The measuring instrument used was a questionnaire on both variables. Data processing was carried out by editing, coding, scoring, and tabulating, while data were analyzed using the Wilcoxon test. Results: Results obtained p value = 0.000 (<0.005), indicating that H1 was accepted. It means that there was an effect of Family Psychoeducation (FPE) therapy on the family's ability to care for children who experienced sexual abuse (post sexual abuse) in the working area of Women's Crisis Center, Jombang Regency. Conclusion: This study concludes that the most common case of sexual abuse is sexual violence. The results show that there is an effect of family psychoeducation (FPE) therapy on the family’s ability to care for children who experienced sexual abuse (post sexual abuse).